불확실성에 대한 인내력 부족이 특성화고등학생의 진로결정수준에 미치는 영향: 취업불안과 계획된 우연기술의 조절된 매개효과 - 정유영; Jeong You Young; 하정희; Ha Jung Hee (청소년복지연구, 2021)
본 연구는 계획적 우연기술에 의해 조절된 취업불안이 특성화고등학생의 불확실성에 대한 인내력 부족과 진로결정수준의 관계에 미치는 매개효과 분석을 실시하였다. 이를 위해 국내 특성화고등학생 300명을 대상으로 불확실성에 대한 인내력 부족, 취업불안, 계획된 우연기술, 진로결정수준에 대한 설문조사를 진행하였다. 데이터는 SPSS 25.0과 Hayes(2013)의 SPSS Process macro를 사용하였다. 주요 결과는 다음과 같다. 첫째, 특성화고등학생의 불확실성에 대한 인내력 부족과 진로결정수준의 관계에서 취업불안의 부분매개효과가 유의하게 나타났다. 둘째, 특성화고 등학생의 불확실성에 대한 인내력 부족과 취업불안의 관계에서 계획된 우연기술의 조절효과가 유의하게 나타났다. 셋째, 특성화고등학생의 불확실성에 대한 인내력 부족과 진로결정수준의 관계에서 계획된 우연기술에 의해 조절된 취업불안의 매개효과가 유의하게 나타났다. 이상의 결과를 기반으로, 특성화고등학생의 진로결정수준을 높이기 위해 불확실성에 대한 인내력을 키우고 취업불안을 낮출 수 있는 방안으로써 계획된 우연기술의 필요성에 대해 논의하였다. The purpose of this study is to verify the mediating effect of job-seeking anxiety moderated by planned happenstance skills on the relationship between the intolerance of uncertainty and career decision level of specialized high school students. For doing this, a questionnaire survey was conducted and data from 300 specialized high school students were analyzed using SPSS 25.0 and SPSS Process macro. Main results are as follows. First, it was confirmed that the job-seeking anxiety had partial mediating effect on the relationship between the intolerance of uncertainty and career decision level. Second, planned happenstance skills played a moderating role in the relationship between the intolerance of uncertainty and job-seeking anxiety. Third, the mediating effect of job-seeking anxiety was moderated by planned happenstance skills in the relationship between the intolerance of uncertainty and career decision level. Based on these results, the so as to heighten career decision level of specialized high school students, the need of planned happenstance skills as a way to reinforce the level of tolerance for uncertainty and to lower job-seeking anxiety was discussed.